Potret analisis difusi inovasi dalam publikasi artikel ilmiah di Lentera Pustaka - Siti Mas Fuah; Roro Isyawati Permata Ganggi (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction. The relationship between the diffusion of innovation and the scientific publication is in the process of scientific communication through media that records previous knowledge from research. The purpose of this study is to show stages of innovation adoption from the articles in one academic journal namely Lentera Pustaka. Data Collection Methods. This study used qualitative research approach with descriptive analysis. Data collection techniques were conducted through observations, interviews, and document study. Informants were selected using a purposive sampling technique. Data Analysis. We analysed the data by reducing, presenting, and drawing conclusions or verification. Results and Discussion. Innovations or new ideas from articles that have been adopted and implemented, are key points. The stage of adopting innovations from scientific articles starts from the published findings, then the adopters produce new knowledge from pre-existing knowledge. Conclusion. The stages of adoption of article innovation in Lentera Pustaka include knowledge, persuasion, decision making, implementation, and confirmation. The editorial board of Lentera Pustaka can ask eaders to participate in the survey related to the interests of proposed research topics. This research shows that articles in scientific journals can be a solution to scientific problems.